Enhancing Maize (Zea mays L.) Growth Through Inoculation with Arbuscular Mycorrhizal Fungi (AMF) - Farmawaty, Farmawaty; Wambrauw, Daniel Z.K.; Suyono, Ign. Joko; Rahayu, Irma (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
This study aims to analyze the effects of arbuscular mycorrhizal fungi (AMF) inoculation on the growth and yield of maize (Zea mays L.) as a solution to fertilizer shortages in Indonesia. The continuous use of inorganic fertilizers can degrade soil quality, making environmentally friendly alternatives, such as biofertilizers, necessary. The study observed the growth optimization of several corn varieties inoculated with AMF. The eight-month study was conducted in the Biology Laboratory at Cenderawasih University's Faculty of Mathematics and Natural Sciences using a pot culture method with three varieties of maize: regular maize (RM), sweet corn (SC), and butter sweet corn (BSC). Parameters observed included plant height, leaf number, and relative growth rate based on dry weight. The results showed that AMF inoculation significantly increased corn plant height by 21.56%, leaf number by 18.14%, and the relative growth rate by 1,425% at six weeks after planting. Butter sweet corn and sweet corn responded better to AMF inoculation than regular corn. The best results occurred when butter sweet corn was given 15 g of AMF inoculum per polybag.